Groundwater prospects in basaltic formations of Mangaon, Raigad district from electrical resistivity imaging technique - Gupta, Gautam; Erram, Vinit C.; Kadam, B. D.; Laxminarayana, M. (My University, 2016)
A two-dimensional resistivity survey was conducted using the Wenner–Schlumberger configuration in the premises of Vijaya Gopal Gandhi Primary and Secondary Ashramshala, Utekhol in Mangaon, Maharashtra. Measurements of three profiles were studied with an aim to delineating the groundwater potential by studying the degree of weathering and fracturing in the weathered profile developed above the basement. The measured resistivity data were inverted using the RES2DINV software. Results from the 2D inverse models of resistivity variation with depth suggest the occurrence of potential aquifer mostly in weathered/ fractured zones within the traps or below it. In addition, the resistivity models produced indicate the presence of saturated fracture zone that could be exploited for groundwater extraction. Vertical electrical sounding measurement using the Schlumberger arrangement was conducted at two locations, which substantiate the 2D model results.
Keywords: Groundwater; Electric resistivity; Aquifer; Deccan Traps; Electrical resistivity imaging; Maharashtra